Urban legends series: oral leukoplakia. (4th February 2013) - Arduino, PG; Bagan, J; El‐Naggar, AK; Carrozzo, M
<x xml:space="preserve">Abstract</x> To date, the term oral leukoplakia (OL) should be used to recognize 'predominantly white plaques of questionable risk, having excluded (other) known diseases or disorders that carry no increased risk of cancer'. In this review, we addressed four controversial topics regarding oral leukoplakias (OLs): (i) Do tobacco and alcohol cause OLs?, (ii) What percentage of OLs transform into oral squamous cell carcinoma (OSCC)?, (iii) Can we distinguish between premalignant and innocent OLs?, and (iv) Is proliferative verrucous leukoplakia (PVL) a specific entity or just a form of multifocal leukoplakia? Results of extensive literature search suggest that (i) no definitive evidence for direct causal relationship between smoked tobacco and alcohol as causative factors of OLs, (ii and iii) the vast majority of OLs follow a benign course and do not progress into a cancer, and no widely accepted and/or validated clinical and/or biological factors can predict malignant transformation, and (iv) the distinction between multifocal/multiple leukoplakias and PVL in their early presentation is impossible; the temporal clinical progression and the high rate of recurrences and development of cancer of PVL are the most reliable features for diagnosis.